Development and validation of speed loss for a blunt-shaped ship in two rough sea voyages in the Southern Hemisphere. (15th September 2017) - Sasa, Kenji; Faltinsen, Odd Magnus; Lu, Li-Feng; Sasaki, Wataru; Prpić-Oršić, Jasna; Kashiwagi, Masashi; Ikebuchi, Takuro
Abstract: Maritime transportation is becoming increasingly complex owing to the fluctuation of oil prices, the introduction of environmental guidelines, and the onset of climate change. Although optimal routing has been researched for decades, few studies have investigated speed loss in rough waves for ships with blunt shape and low speed. Onboard measurement of a 28, 000DWT bulk carrier has been conducted for six years in rough sea voyages in the Southern Hemisphere. It is necessary to validate the wave and wind conditions in order to discuss speed loss in these situations. Here, numerical simulation of speed loss is developed and conducted for each estimated wave condition. The speed losses under different numerical models of added resistance are quantitatively compared in two rough sea voyages. The simulated results of speed loss are in good agreement with the measured results if the estimated wave is accurate and the wave direction is properly defined. The speed loss accuracy is significantly influenced by the wave estimation accuracy or wave direction setting compared to that in the numerical models of added resistance in actual seas. Simulated results provide important information to evaluate the performance of a ship with blunt shape in rough waves. Abstract : Highlights: This study makes clear the multiple speed losses in rough waves in the Southern Hemisphere. The accuracy of speed loss is compared among seakeeping models of added resistance. Differences of ship's speed are 0–5 knots, strongly influenced by weather hindcasting. Speed loss can be evaluated if the hindcasting models and wave direction is properly defined.